integral of xe^-x dx

Using integration by parts by letting u=x and dv/dx=e^-x. this implies that du/dx=1 and v=-e^-xThe By Parts formulae is u.v - integral(v.du/dx) = -xe^-x - integral(-e^-x).1 dx = -xe^-x + integral(e^-x) dx = -xe^-x -e^-x +c (where c is the constant of integration.)

Answered by Brandon K. Maths tutor

5088 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What is a stable solution and what is dominance?


express (1+4(root7)) / (5+2(root7)) as a+b(root7), where a and b are integers


Find the area under the curve y = (4x^3) + (9x^2) - 2x + 7 between x=0 and x=2


Where does the quadratic formulae come from?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences